Play, playfulness, creativity and innovation - Bateson, P. P. G. (Paul Patrick Gordon), 1938-; Martin, Paul, 1958 May 11- (Cambridge ; New York : Cambridge University Press, 2013)
"What role does playful behaviour and playful thought take in animal and human development? How does play relate to creativity and, in turn, to innovation? Unravelling the different meanings of 'play', this book focuses on non-aggressive playful play. The authors emphasise its significance for development and evolution, before examining the importance of playfulness in creativity. This discussion sheds new light on the links between creativity and innovation, distinguishing between the generation of novel behaviour and ideas on the one hand, and the implementation of these novelties on the other. The authors then turn to the role of play in the development of the child and to parallels between play, humour and dreaming, along with the altered states of consciousness generated by some psychoactive drugs. A final chapter looks forward to future research and to what remains to be discovered in this fascinating and important field"--
1. Introduction -- 2. The biology of play -- 3. The functions of play -- 4. Evolution and play -- 5. Creativity in humans -- 6. Animals finding novel solutions -- 7. People and organisations -- 8. Childhood play and creativity -- 9. Humour and playfulness -- 10. Dreams, drugs and creativity -- 11. Pulling the threads together.
Includes bibliographical references (pages 135-149) and index.
Keywords: Play -- Psychological aspects; Creative ability; Creative thinking; MEDICAL / Veterinary Medicine / General; Spiel; 2; Kreatives Denken; Entwicklungspsychologie; Creative ability; Creative thinking; Play -- Psychological aspects